Diverse Effects of Hypothermia Therapy in Patients with Severe Traumatic Brain Injury Based on the Computed Tomography Classification of the Traumatic Coma Data Bank - Suehiro, Eiichi (J Neurotrauma, 2015)
A multicenter randomized controlled trial of patients with severe traumatic brain injury who received therapeutic hypothermia or fever control was performed from 2002 to 2008 in Japan (BHYPO). There was no difference in the therapeutic effect on traumatic brain injury between the two groups. The efficacy of hypothermia treatment and the objective of the treatment were reexamined based on a secondary analysis of the BHYPO trial in 135 patients (88 treated with therapeutic hypothermia and 47 with fever control). This analysis was performed to examine clinical outcomes according to the CT classification of the Traumatic Coma Data Bank on admission. Clinical outcomes were evaluated with the Glasgow Outcome Scale and mortality at 6 months after injury. Good recovery and moderate disability were defined as favorable outcomes. Favorable outcomes in young patients (≤50 years old) with evacuated mass lesions significantly increased from 33.3% with fever control to 77.8% with therapeutic hypothermia. Patients with diffuse injury III who were treated with therapeutic hypothermia, however, had significantly higher mortality than patients treated with fever control. It was difficult to control intracranial pressure with hypothermia for patients with diffuse injury III, but hypothermia was effective for young patients with an evacuated mass lesion.